Marine heatwaves: a new insight of climate change: the combined effect with Carbamazepine upon Mytilus galloprovincialis - Costa, Silvana Teixeira (2021)
Marine coastal systems are among the main climate change targets. In particular, an increasing concern has raised on the impacts caused by weather events, namely marine heatwaves (MHWs), towards organisms from these areas. MHWs are periods of extreme warm sea surface temperature that persist for days to months and can extend up to thousands of kilometres. Some of the recently observed MHWs revealed the high vulnerability of marine ecosystems and fisheries to such extreme climate events. Beside thermal aggression, inhabiting organisms are also exposed to several pollutants that reach the aquatic compartment and constitute potential hazardousness. Furthermore, it is already reported in literature that warming may affect chemicals’ bioavailability and speciation, changing pollutants toxicity, but temperature rise may also change organism’s sensitivity to pollutants. Nevertheless, limited information is reported regarding MHWs impacts on wildlife and how they cope with pollutants, namely pharmaceuticals such as the case of Carbamazepine (CBZ). Carbamazepine is a pharmaceutical of emerging concern, found in aquatic systems in concentrations ranging from ng/L to µg/L. For this, mussels Mytilus galloprovincialis were chosen as model organisms to develop the present research study. Organisms were exposed to two different climatic scenarios: an optimal scenario where organisms were subjected to 18 ºC water temperature for 20 days and a heatwave scenario ranging between 18 ºC to 22.5 ºC that lasted 11 days (temperature peak at day 6), followed by a recovery period of 10 days (constant temperature 18 ºC). The impacts caused by MHW were evaluated alone and in combination with CBZ contamination of 1 µg/L corresponding to four different treatments: controls (CTL), Carbamazepine exposure (CBZ), marine heatwave scenario (MHW) and the combination of both stressor (CBZ + MHW). Carbamazepine bioaccumulation was assessed and biological impacts were evaluated considering a wide battery of toxicological biomarkers. The results obtained revealed a clear synergism of MHW treatment on CBZ uptake. However, interactions between temperature and CBZ exposure had effects on induction of antioxidant responses, data showed a time dependent impact. Nevertheless, a general impairment was observed between total oxidative scavenging capacity, glutathione dependent parameters, fatty acids metabolism and malondialdehyde content. Significant variations of the immune system were mainly caused by multiple exposure (CBZ + MHW), specially for Micronuclei test. Moreover, MHW showed to be much more effective in what concerns DNA damage in haemocytes. The overall results confirmed that MHWs could influence ecotoxicological effects of environmental contaminants, praising the concern of developing more and better researches in order to understand cellular mechanisms and predict toxicological responses of marine organisms of economic relevance and public health concern.